Identifikasi Potensi Bahaya Serta Cara Mencegahnya pada Unit Kilang di PPSDM MIGAS CEPU - ahmat danang wahyuni danang (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2023)
ABSTRACT PPSDM Migas has implemented occupational safety and health (K3 PPSDM Migas has providing Personal Protective Equipment (PPE) in every line of the company, especially at the PPSDM refinery Oil and gas, first aid in accidents (P3K), protection and prevention of hazards fire, form a team of firefighters, prepare fire extinguishers.Potential danger at the 1st CEPU MIGAS PPSDM Refinery unit in the Pump Work Area Centrifuges that have potential hazards in the form of hearing, slipping, getting caught in an electric current with the potential for disease in the form of ringing in the ears, deafness, sprains, wounds, fractures, wounds burn.2 in the Furnance/Furnace Work Area which has a potential hazard in the form of fire and explosion, slip, fall, hearing with the potential for disease in the form of burns, sprains, injuries broken bones, ears will be deaf. 3 in the Cooling Tower Work Area with potential hazards in the form of falls, leaks with potential disease in the form of Sprains, fractures.4 in the Unit Work Area Oil Catcher trap with potential dangers in the form of respiratory problems, slipping, tripping, with potential diseases in the form of respiratory disorders, minor injuries, sprains.5 in the Pump Work Area reciprocating / Thoracic with potential dangers in the form of hearing, slipping, blistering, with potential diseases in the form of deafness, sprains, bruises, ringing in the ears.6 in the HE Work Area (Heat Exchanger) with a potential hazard in the form of fire and explosion, slipping, with the potential for the disease is in the form of burns, severe injuries, amplification, sprains, fractures. 7 in the Storage Work Area Tanks with potential hazards in the form of potential diseases in the form of falls, fires and explode with potential disease in the form of sprains, fractures, skin irritation. 8 in the Work Area Sampling points with potential hazards in the form of slips, skin irritation, fire, disturbances with the potential for disease in the form of sprains, injuries, fractures, itching in skin, burns.9 in the Trench / Sewer Work Area with a potential hazard in the form of falling with potential disease in the form of cidraringan and sprains. Keywords: potential hazard in the refinery